2000
DOI: 10.1093/brain/123.6.1203
|View full text |Cite
|
Sign up to set email alerts
|

Movement-related change of electrocorticographic activity in human supplementary motor area proper

Abstract: We investigated movement-related change in the cortical EEG signal by simultaneous recording from the primary sensorimotor area (S1-M1) and the supplementary motor area proper (SMA proper) in four patients with intractable partial epilepsy. By the use of temporal spectral evolution (TSE) analysis, the change in background cortical activity in relation to self-paced finger/wrist extension was compared among the SMA proper, S1 and M1. All three areas showed a decrease in the amount of activity for the frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
108
4
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(133 citation statements)
references
References 68 publications
19
108
4
2
Order By: Relevance
“…The behavior of the present LFPOs shows similarities with cerebral "resting" rhythmic activities of wakefulness arresting to sensory or motor information, such as ␣ and rhythms. Oscillations most often occur during a premovement period and cease around movement onset (Donoghue et al, 1998;Ohara et al, 2000;Pfurtscheller et al, 2003). The decrease in -oscillation approximately coincides with the increase in ␥ oscillation above 30 Hz (Pfurtscheller et al, 2003) and with the appearance of firing rate modulation coupled with the motor action (Donoghue et al, 1998).…”
Section: Physiological Role Of 160 Hz Oscillationsmentioning
confidence: 89%
“…The behavior of the present LFPOs shows similarities with cerebral "resting" rhythmic activities of wakefulness arresting to sensory or motor information, such as ␣ and rhythms. Oscillations most often occur during a premovement period and cease around movement onset (Donoghue et al, 1998;Ohara et al, 2000;Pfurtscheller et al, 2003). The decrease in -oscillation approximately coincides with the increase in ␥ oscillation above 30 Hz (Pfurtscheller et al, 2003) and with the appearance of firing rate modulation coupled with the motor action (Donoghue et al, 1998).…”
Section: Physiological Role Of 160 Hz Oscillationsmentioning
confidence: 89%
“…Mu power is reduced during both action observation and execution. Mu is most powerful in the primary somatosensory cortex (SI) (Salmelin et al, 1995;Ohara et al, 2000;Caetano et al, 2007); however, we lack evidence for the assumption that regions of the MNS, the ventral premotor cortex in particular (Pineda, 2005), are responsible for -modulation and that fMRI and -suppression experiments measure the functioning of the same MNS. Elegant MEG experiments also investigated an ϳ20 Hz -component which rebounds after action observation and execution (Hari et al, 1998), but because optimal designs to study 10 Hz and 20 Hz components differ, we focus here on the most studied, 10 Hz component, and will use as shorthand for that component alone.…”
Section: Introductionmentioning
confidence: 95%
“…Indeed, the extended frequency response of invasive EEG recordings has shown that during functional activation of cerebral cortex, gamma activity occurs over a much broader range of frequencies that extend far beyond the traditional 40-Hz gamma band typically observed in scalp EEG (Crone et al, 1998a;Crone et al, 2006). These non-phase-locked responses in "high-gamma" frequencies, typically greater than 60 Hz and extending as high as 200 Hz, have been observed during functional activation in a variety of cortical domains, including sensorimotor (Crone et al, 1998a;Ohara et al, 2000;Pfurtscheller et al, 2003;Leuthardt et al, 2004), oculomotor (Lachaux et. al., 2006), auditory (Crone et al, 2001a;Ray et al, 2003;Edwards et al, 2005), visual (Crone et al, 2001b;Lachaux et al, 2005;Tanji et al, 2005), and language (Crone et al, 2001b;Sinai et al, 2005) cortices.…”
Section: Introductionmentioning
confidence: 99%